Targeted On-Demand Screening of Pesticide Panel in Soil Runoff - Dhamu, Vikram Narayanan; Sukumar, Suhashine; Kadambathil, Crisvin Sajee; Muthukumar, Sriram; Prasad, Shalini (Frontiers in Chemistry, 2021)
Pesticides are applied as a common agricultural and horticultural practice so as to serve as a control against weeds, fungi, and insects in plant systems. Application of these chemical agents is usually by spraying it on the crop or plant. However, this methodology is not highly directional and so only a fraction of the pesticide actually adsorbs onto the plant-and the rest seeps through into the soil base contaminating its composition and eventually leaching into ground water sources. Electrochemical sensors which are more practical for in-situ analysis used for pesticide detection in soil run-off systems are still in dearth while the ones published in literature attributed with complex sensor modification/functionalization and pre-processing of samples. Hence, in this work- we present a highly intuitive electroanalytical sensor approach towards rapid (10 minutes), on-demand screening of commonly used pesticides- Glyphosate and Atrazine in soil run-off. The proposed sensor functions based on affinity biosensing mechanism driven via thiol-crosslinker and antibody receptors that holistically behaves as a recognition immunoassay stack that is specific and sensitive to track test pesticide analytes. Then, this developed sensor is integrated further to create a pesticide sensing ecosystem by means of a front-end field-deployable smart device. The method put forward in this work is compared and validated against standard laboratory potentiostat instrument to determine efficacy, feasibility and robustness for a point-of-use (PoU) setting yielding LoD levels of 0.001 ng/mL for Atrazine and 1ng/mL for Glyphosate; Also, the ML model integration resulted in accurate prediction rate ≈80% in real-soil samples. Thereby, a universal pesticide screening analytical device is designed, fabricated and tested for pesticide assessment in real soil run-off samples.